PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, SELF EFFICACY, DAN WORK ENGAGEMENT TERHADAP PERILAKU KERJA INOVATIF YANG DIMODERASI OLEH LINGKUNGAN KERJA PADA PEGAWAI - Ni Made Febrie Arisandi Alangkajeng; Thatok Asmony; Akhmad Saufi (Master of Management, Mataram University, 2023)
Innovative work behavior can result in constructive conflict, innovation success, and a positive work attitude. Also there is an increase in performance, compatibility between demands and work abilities, job satisfaction, employee welfare, better interpersonal relationships, and increased personal growth. The purpose of this study was to determine the effect of transformational leadership, self-efficacy, and work engagement on innovative work behavior. The sample in this study amounted to 65 samples. The instrument used in this research is a questionnaire. Data were analyzed using Structural Equation Modeling with the help of the Partial Least Square (PLS) program. Based on the results of the study, it can be concluded that transformational leadership, self-efficacy, and work engagement have a positive and significant effect on the innovative work behavior of employees of the West Nusa Tenggara Province Communication, Informatics and Statistics Office. The work environment is able to moderate the relationship between transformational leadership on innovative work behavior of employees of the Information Communication and Statistics Office of the Province of West Nusa Tenggara, while others say that the work environment has not been able to moderate the relationship between self-efficacy and work engagement towards innovative work behavior of employees of the Office of Information Communication and Statistics of the Province of West Nusa Tenggara. Keywords: Transformational Leadership, Self Efficacy, Work Engagement, Innovative Work Behavior, and Work Environment